An insight into pharmaceutical challenges with ionic liquids: where do we stand in transdermal delivery? - Jain, Ankit; Shakya, Ashok K.; Prajapati, Shiv Kumar; Eldesoqui, Mamdouh; Mody, Nishi; Jain, Sanjay K.; Naik, Rajashri R.; Patil, Umesh K. (Frontiers in Bioengineering and Biotechnology, 2024)
Ionic liquids (ILs) represent an exciting and promising solution for advancing drug delivery platforms. Their unique properties, including broad chemical diversity, adaptable structures, and exceptional thermal stability, make them ideal candidates for overcoming challenges in transdermal drug delivery. Despite encountering obstacles such as side reactions, impurity effects, biocompatibility concerns, and stability issues, ILs offer substantial potential in enhancing drug solubility, navigating physiological barriers, and improving particle stability.To propel the use of IL-based drug delivery in pharmaceutical innovation, it is imperative to devise new strategies and solvents that can amplify drug effectiveness, facilitate drug delivery to cells at the molecular level, and ensure compatibility with the human body. This review introduces innovative methods to effectively address the challenges associated with transdermal drug delivery, presenting progressive approaches to significantly improve the efficacy of this drug delivery system.